Factors of Non-Adherence to Antihypertensive Medicine in the Elderly Population - Nafees, Neelam; Ghani, Mansoor; Nafees, Nabila; Kausar, Samina (Biological and Clinical Sciences Research Journal, 2025)
Hypertension is a leading cause of cardiovascular morbidity and mortality, particularly among the elderly. Despite the availability of effective antihypertensive therapies, medication non-adherence remains a major barrier to optimal blood pressure control. Understanding the multifactorial determinants of non-adherence among elderly hypertensive patients in low- and middle-income countries like Pakistan is essential for designing targeted interventions. Objective: To identify the factors contributing to non-adherence to antihypertensive medication among elderly hypertensive patients attending tertiary care hospitals in Lahore, Pakistan. Methods: A cross-sectional descriptive study was conducted at four public sector hospitals in Lahore from September 2019 to March 2020. A total of 200 hypertensive patients aged ≥60 years were recruited through purposive sampling. Data were collected using two standardized tools—the Drug Attitude Inventory-10 (DAI-10) and the Modified Drug Adherence Work-Up Tool (M-DRAW)—translated into Urdu and validated for internal consistency (Cronbach's α = 0.70 and 0.758, respectively). Descriptive statistics were used to summarize demographic data. In contrast, chi-square, independent t-tests, and ANOVA with post hoc Tukey's test were used to determine associations between demographic and adherence-related variables in SPSS version 20. A p-value <0.05 was considered statistically significant. Results: The mean age of participants was 66.74 ± 5.39 years; 52% were male, and 54.5% had no formal education. Most patients (73.5%) had been under treatment for >6 months, and 53.5% were taking three antihypertensive medications. The majority (68.5%) exhibited unintentional non-adherence, while 31.5% demonstrated intentional non-adherence. Financial burden (50%), pill burden (60.5%), and difficulty in maintaining medication schedules were the most frequent barriers. Condition-related factors (mean 3.0 ± 0.7) were the most significant contributors, followed by patient-related and socioeconomic factors (p< 0.001). Significant associations were found between perceived benefit of therapy and education level (p = 0.017), dose adjustment and number of tablets (p = 0.010), and gender with treatment doubts (p = 0.018). Beliefs and health perceptions more strongly influenced intentional non-adherence, whereas unintentional non-adherence was associated with financial and regimen-related constraints. Conclusion: Non-adherence to antihypertensive medication among elderly patients is a multifaceted issue influenced by socioeconomic, educational, psychological, and treatment-related factors. Condition-related beliefs and patient-related perceptions play a dominant role, particularly in intentional non-adherence. Interventions should focus on patient education, simplifying medication regimens, enhancing family and social support, and providing financial assistance to improve long-term adherence and reduce hypertension-related complications in elderly populations.